2010
DOI: 10.1186/1471-2148-10-201
|View full text |Cite
|
Sign up to set email alerts
|

Rampant historical mitochondrial genome introgression between two species of green pond frogs, Pelophylax nigromaculatus and P. plancyi

Abstract: BackgroundMitochondrial introgression may result in the mitochondrial genome of one species being replaced by that of another species without leaving any trace of past hybridization in its nuclear genome. Such introgression can confuse the species genealogy estimates and lead to absurd inferences of species history. We used a phylogenetic approach to explore the potential mitochondrial genome introgression event(s) between two closely related green pond frog species, Pelophylax nigromaculatus and P. plancyi.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(100 citation statements)
references
References 41 publications
(69 reference statements)
8
85
1
Order By: Relevance
“…As expected, P. nigromaculatus and P. plancyi formed the sister clade to P. ridibundus and P. lessonae, with substantial divergence (15.8%) between western and eastern Palaearctic representatives of the genus. The low sequence divergence between P. nigromaculatus and P. plancyi (2.1%), suggestive of intraspecific variation, may be the result of mitochondrial transfer between the two taxa, as recently proposed by Liu et al (2010) who postulated both ancient and recent introgression events between these two species.…”
Section: Mitogenome Composition and Divergencementioning
confidence: 81%
“…As expected, P. nigromaculatus and P. plancyi formed the sister clade to P. ridibundus and P. lessonae, with substantial divergence (15.8%) between western and eastern Palaearctic representatives of the genus. The low sequence divergence between P. nigromaculatus and P. plancyi (2.1%), suggestive of intraspecific variation, may be the result of mitochondrial transfer between the two taxa, as recently proposed by Liu et al (2010) who postulated both ancient and recent introgression events between these two species.…”
Section: Mitogenome Composition and Divergencementioning
confidence: 81%
“…However, it is well known that gene flow can extend beyond species boundaries in amphibians, especially among closely-related forms (e.g. Liu et al 2010;Hedrick 2013;Zieliński et al 2013) and might not be accurately described by mitochondrial markers (Irwin 2002;Currat et al 2008). Hence, phylogeographic comparative analyses of units defined by equivalent divergence times, ideally determined from multiple unlinked nuclear loci, will outperform analyses based on species units and ultimately reveal the effects of natural history and ecological variables on population genetic divergence.…”
Section: Proximate Causes Of Population Divergencementioning
confidence: 96%
“…For instance, sex-biased dispersal, mating and offspring production is a common explanation for mito-nuclear discordance, but behavioural and crossing data have only been collected for a handful of systems. For example, in a genetic survey of the dark-spotted frog (Rana nigromaculata), Liu et al (2010) found that many populations are fixed for the eastern golden frog's (R. plancyi) mtDNA. Data combined from the field and laboratory suggest that all F1 males were sterile, but that females were partially fertile, consistent with Haldane's rule and with patterns of mito-nuclear discordance in natural populations (Liu et al 2010).…”
Section: Untangling Processes Driving Discordance From Biogeographic mentioning
confidence: 99%
“…For example, in a genetic survey of the dark-spotted frog (Rana nigromaculata), Liu et al (2010) found that many populations are fixed for the eastern golden frog's (R. plancyi) mtDNA. Data combined from the field and laboratory suggest that all F1 males were sterile, but that females were partially fertile, consistent with Haldane's rule and with patterns of mito-nuclear discordance in natural populations (Liu et al 2010). Unfortunately, these data are difficult to collect in many systems, and researchers instead rely on more general patterns.…”
Section: Untangling Processes Driving Discordance From Biogeographic mentioning
confidence: 99%